Epidemiology, Comorbidity, and Behavioral Genetics of Antisocial Personality Disorder and Psychopathy - Werner, Kimberly B. (Psychiatr Ann, 2015)
Psychopathy is theorized as a disorder of personality and affective deficits while antisocial personality disorder (ASPD) diagnosis is primarily behaviorally based. While ASPD and psychopathy are similar and are highly comorbid with each other, they are not synonymous. ASPD has been well studied in community samples with estimates of its lifetime prevalence ranging from 1-4% of the general population.(4,5) In contrast, psychopathy is almost exclusively investigated within criminal populations so that its prevalence in the general population has been inferred by psychopathic traits rather than disorder (1%). Differences in etiology and comorbidity with each other and other psychiatric disorders of these two disorders are also evident. The current article will briefly review the epidemiology, etiology, and comorbidity of ASPD and psychopathy, focusing predominately on research completed in community and clinical populations. This paper aims to highlight ASPD and psychopathy as related, but distinct disorders.